Factors Affecting The Implementation Of SAK EMKM In Restaurant Business At Banyumas Regency - Dimas Arya Denta; Eko Suyono; Rini Widianingsih (Jurnal Indonesia Sosial Teknologi, 2023)
This research is quantitative research in the restaurant business at Banyumas Regency. This research takes the title "Factors Affecting the Implementation of SAK EMKM in Restaurant Business at Banyumas Regency". The purpose of this research was to determine the implementation of SAK EMKM in the restaurant business at Banyumas Regency. Retrieval of data used in this research through a survey approach. The respondents in this research were business actors/employees. The data used was primary data in the form of result data from the questionnaires distributed and secondary data in the form of data on the number of restaurants in Banyumas Regency which came from the Badan Pusat Statistik Jawa Tengah. For data analysis using descriptive analysis, classic assumption test, and hypothesis test. The results of this research indicate that accounting socialization has a significant positive effect on the implementation of SAK EMKM in business restaurants at Banyumas Regency, while business scale and accounting knowledge have a significant negative effect on the implementation of SAK EMKM in business restaurants at Banyumas Regency